Pengaruh Perencanaan Pajak, Profitabilitas, dan Ukuran Perusahaan Terhadap Manajemen Laba - Citra Kharisma Putri Tias; Dirvi Surya Abbas; Mohamad Zulman Hakim (Journal Economic Excellence Ibnu Sina, 2023)
The purpose of this study is to determine the effect of Tax Planning, Profitability, Company Size on Earnings Management in property, real estate, and building construction sector companies in Indonesia Period 2016 -2021.This study uses descriptive research with a quantitative approach. The population in this study is 65 companies in the property, real estate and building construction sectors that have been and are still listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling and obtained a sample of 9 companies in the property, real estate and building construction sectors. The analytical method used is panel data regression analysis using Eviews version 12 software. In this study the dependent variable (Y) and the independent variable Earnings Management and namely tax planning (X1), profitability (X2) and company size (X3) as well as moderating variables. The results showed that tax planning and profitability had no effect on earnings management, while profitability and company size had a positive effect on earnings management.